MAIN ELEMENTS OF TAXATION IN THE CONDITIONS OF THE DEVELOPMENT OF DIGITAL ECONOMY - TSINDELIANI, I A; ANISINA, K. T; BUROVA, A. S.; KOPINA, A. A.; MIGACHEVA, E. V.; RODYGINA, V. E. (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT The purpose of this article is to consider the main elements of taxation in a digital economy. On the base of the analysis, it was concluded that in conditions of digital economy, the development of information resources would provide a concretization of the provisions of the main elements of taxation and optimize the emergence and pursuance of the constitutional duties to pay taxes, as well as the calculation of tax amounts. The main provisions and conclusions can be used in scientific and practical activities when considering the issues of the legal construction of taxes. RESUMEN El propósito de este artículo es la consideración de los principales elementos de los impuestos en una economía digital. Sobre la base del análisis del estudio, se concluyó que, en condiciones de economía digital, el desarrollo de los recursos de información proporciona una concreción de las disposiciones de los principales elementos de la tributación y optimiza la aparición y el cumplimiento de los deberes constitucionales de pagar impuestos., así como el cálculo de los importes de impuestos. Las principales disposiciones y conclusiones pueden utilizarse en actividades científicas y prácticas al considerar los problemas de la construcción legal de impuestos.